Hadis Riwayat Ibnu Majah No. 639 Tentang Larangan Bersenggama Saat Istri Haid: Studi Kasus Penyebab Kista Ovarium - Nofalia Cindi Anggraeni; Muhid (El-Sunnah)
Abstract. This article discusses the prohibition of intercourse during menstruation as mentioned in the hadith narrated by Ibn Majah no. 639. In this research, the researcher investigates why this prohibition was proclaimed by the Prophet Muhammad Saw from a medical perspective as proof (I'jaz al-‘Ilmi). Using qualitative research methods and descriptive analysis, the researcher conducted interviews with midwives and healthcare workers at Bhayangkara Police Hospital, Surabaya. The research findings revealed that engaging in sexual intercourse during menstruation increases the risk of developing ovarian cysts. This is because the menstrual blood, which is supposed to leave the body through the vagina, is forced to reverse back into the body due to the intercourse. Additionally, contaminants such as bacteria on the labia (vaginal lips) are carried into the body, where they can cause infections, leading to inflammation and, eventually, the formation of cysts. Based on these findings, it can be concluded that the Prophet Muhammad’s Saw words have an underlying rationale. This emphasizes the need for an interdisciplinary approach when studying religious texts so that broader research results can be achieved, rather than relying solely on a textual approach.